Manipulation of NKG2D ligands by cytomegaloviruses: impact on innate and adaptive immune response - Jonjic, Stipan (Frontiers in Immunology, 2011)
NKG2D is a potent activating receptor expressed on NK cells, NKT cells, γδ T cells and CD8 T cells. NKG2D recognizes cell surface molecules structurally related to MHC class I proteins induced by infection or other type of cellular stress. The engagement of NKG2D leads to NK cell cytotoxicity and cytokine secretion or to a co-stimulation of CD8 T cells. Both human and mouse cytomegalovirus (CMV) have evolved numerous mechanisms to evade NKG2D-mediated immune response. This review describes the mechanisms used by CMV to inhibit NKG2D ligand expression and the recent advances in exploiting the NKG2D recognition pathway for mounting efficient and long-lasting immune response.